A Recently Assembled Degradation Pathway for 2,3-Dichloronitrobenzene in Diaphorobacter sp. Strain JS3051 - Tao Li; Yi-Zhou Gao; Jia Xu; Shu-Ting Zhang; Yuan Guo; Jim C. Spain; Ning-Yi Zhou (mBio, 2021)
ABSTRACT Diaphorobacter sp. strain JS3051 utilizes 2,3-dichloronitrobenzene (23DCNB), a toxic anthropogenic compound, as the sole carbon, nitrogen, and energy source for growth, but the metabolic pathway and its origins are unknown. Here, we establish that a gene cluster (dcb), encoding a Nag-like dioxygenase, is responsible for the initial oxidation of the 23DCNB molecule. The 2,3-dichloronitrobenzene dioxygenase system (DcbAaAbAcAd) catalyzes conversion of 23DCNB to 3,4-dichlorocatechol (34DCC). Site-directed mutagenesis studies indicated that residue 204 of DcbAc is crucial for the substrate specificity of 23DCNB dioxygenase. The presence of glutamic acid at position 204 of 23DCNB dioxygenase is unique among Nag-like dioxygenases. Genetic, biochemical, and structural evidence indicate that the 23DCNB dioxygenase is more closely related to 2-nitrotoluene dioxygenase from Acidovorax sp. strain JS42 than to the 34DCNB dioxygenase from Diaphorobacter sp. strain JS3050, which was isolated from the same site as strain JS3051. A gene cluster (dcc) encoding the enzymes for 34DCC catabolism, homologous to a clc operon in Pseudomonas knackmussii strain B13, is also on the chromosome at a distance of 2.5 Mb from the dcb genes. Heterologously expressed DccA catalyzed ring cleavage of 34DCC with high affinity and catalytic efficiency. This work not only establishes the molecular mechanism for 23DCNB mineralization, but also enhances the understanding of the recent evolution of the catabolic pathways for nitroarenes. IMPORTANCE Because anthropogenic nitroaromatic compounds have entered the biosphere relatively recently, exploration of the recently evolved catabolic pathways can provide clues for adaptive evolutionary mechanisms in bacteria. The concept that nitroarene dioxygenases shared a common ancestor with naphthalene dioxygenase is well established. But their phylogeny and how they evolved in response to novel nitroaromatic compounds are largely unknown. Elucidation of the molecular basis for 23DCNB degradation revealed that the catabolic pathways of two DCNB isomers in different isolates from the same site were derived from different recent origins. Integrating structural models of catalytic subunits and enzymatic activities data provided new insight about how recently modified enzymes were selected depending on the structure of new substrates. This study enhances understanding and prediction of adaptive evolution of catabolic pathways in bacteria in response to new chemicals.